(untitled) (International Journal of Engineering and Computer Science, 2017)
Impact analysis is defined as the process of identifying the potential consequences (side-effects) of a change, and estimating what needs to be modified to accomplish a change. We propose a UML model-based approach to impact analysis that can be applied before any implementation of the changes, thus allowing an early decision-making and change planning process. We first verify that the UML diagrams are consistent (consistency check). Then changes between two different versions of a UML model are identified according to a change taxonomy, and model elements that are directly or indirectly impacted by those changes (i.e., may undergo changes) are determined using formally defined impact analysis rules (written with Object Constraint Language). A measure of distance between a changed element and potentially impacted elements is also proposed to prioritize the results of impact analysis according to their likelihood of occurrence.